2019
DOI: 10.1001/jamanetworkopen.2019.0411
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Gradients and Distribution of Diabetes, Hypertension, and Obesity in India

Abstract: Key Points Question What is the socioeconomic distribution of diabetes, hypertension, and obesity in India, and what are the socioeconomic gradients? Findings In this cross-sectional study of data from the Indian National Family Health Survey of 757 958 individuals, the population burden of cardiovascular disease risk factors was concentrated among groups with higher socioeconomic status. Positive and significant socioeconomic gradients were observed for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 30 publications
10
83
1
Order By: Relevance
“…Prevalence of diabetes was higher amongst higher socio-economic status groups [69][70][71][72] . Thus, higher wealth is an independent risk factor for diabetes 73 .…”
Section: Discussionmentioning
confidence: 91%
“…Prevalence of diabetes was higher amongst higher socio-economic status groups [69][70][71][72] . Thus, higher wealth is an independent risk factor for diabetes 73 .…”
Section: Discussionmentioning
confidence: 91%
“…This is consistent with the strong direct association between adult socio-economic conditions and adiposity observed in India (compared to the weak association for blood pressure). 27…”
Section: Discussionmentioning
confidence: 99%
“…We defined ‘self-report diabetes’ as all non-pregnant individuals who answered ‘yes’ to the question do you currently have diabetes. We defined ‘undiagnosed diabetes’ as participants who answered ‘no’ to the question do you currently have diabetes7 8 and following a laboratory assessment either had an opportunistic fasting glucose level ≥126 mg/dL (referred to as ‘fasting’) or had a random glucose level ≥200 mg/dL (referred to as ‘random’). We define ‘opportunistic fasting’ as individuals who self-reported that they had not eaten or had any calorie intake for 8 or more hours.…”
Section: Methodsmentioning
confidence: 99%